Three isoforms of isoamylase contribute different catalytic properties for the debranching of potato glucans - Hasnain, Hussain; Alexandra, Mant; Robert, Seale; Sam, Zeeman; Edward, Hinchliffe; Anne, Edwards; Christopher, Hylton; Stephen, Bornemann; Alison, M. Smith; Cathie, Martin; Regla, Bustos (US National Library of Medicine National Institutes of Health Search databaseSearch term Search, 2003)
Isoamylases are debranching enzymes that hydrolyze -1,6 linkages in -1,4/ -1,6–linked glucan polymers. In plants, they have been shown to be required for the normal synthesis of amylopectin, although the precise manner in which they influence starch synthesis is still debated. cDNA clones encoding three distinct isoamylase isoforms (Stisa1, Stisa2, and Stisa3) have been identified from potato. The expression patterns of the genes are consistent with the possibility that they all play roles in starch synthesis. Analysis of the predicted sequences of the proteins suggested that only Stisa1 and Stisa3 are likely to have hydrolytic activity and that there probably are differences in substrate specificity between these two isoforms. This was confirmed by the expression of each isoamylase in Escherichia coli and characterization of its activity. Partial purification of isoamylase activity from potato tubers showed that Stisa1 and Stisa2 are associated as a multimeric enzyme but that Stisa3 is not associated with this enzyme complex. Our data suggest that Stisa1 and Stisa2 act together to debranch soluble glucan during starch synthesis. The catalytic specificity of Stisa3 is distinct from that of the multimeric enzyme, indicating that it may play a different role in starch metabolism.